Kretek Sebagai Budaya Asli Indonesia: Telaah Paradigmatik Terhadap Pandangan Mark Hanusz Mengenai Kretek di Indonesia (MUHARRIK: Jurnal Dakwah dan Sosial, 2018)
Hanusz's interest in kretek was very large when he discovered that kretek was the most powerful commodity in Indonesia. His astonishment began when the economic crisis in 1998 struck Indonesia violently to overthrow the Suharto regime. However, the kretek industry remains upright and does not experience obscurity at all. In fact, it tends to continue to exist. Hanusz found that the strength of the kretek industry was because it was supported by strong socio-cultural conditions. Kretek became king in his own palace, namely Indonesia. Starting from raw materials, energy, technology and most importantly the market is in Indonesia itself. This condition triggers the kretek industry to survive for more than 100 years in Indonesia, and makes kretek appropriate to be labeled as the Indonesian heritage.